Perioperative management of massive pulmonary hemorrhage after pulmonary endarterectomy - (:unkn) unknown (My University, 2018)
Background: This study aims to evaluate our approaches and outcomes in patients who developed hemoptysis following pulmonary endarterectomy.Methods: Pulmonary endarterectomy was performed in 460 patients at Kartal Koşuyolu Training and Research Hospital between March 2011 and September 2017. Clinical characteristics, perioperative management and postoperative outcomes of 10 patients (2.1%) (4 males, 6 females; mean age 48.3±16.5 years; range 21 to 76 years) with massive pulmonary hemorrhage following pulmonary endarterectomy were evaluated.Results: Mean period of diagnosis for chronic thromboembolic pulmonary hypertension was 17±13.6 months. All patients were New York Heart Association functional class II (n=2), III (n=5) or IV (n=3). For the treatment of massive pulmonary hemorrhage, intraoperative extracorporeal membrane oxygenation was used in six patients (60%), while conservative treatments were used in four patients (40%). In-hospital mortality rate was 50% (n=5); the causes for mortality were septic shock in two patients, multiple organ failure in two patients and intracranial hemorrhage in one patient. Survival was achieved in two patients on extracorporeal membrane oxygenation and three patients receiving conservative treatment. Functional and hemodynamic improvement was observed in all surviving patients.Conclusion: Despite the relatively low incidence of massive pulmonary hemorrhage after pulmonary endarterectomy, it is a potentially fatal complication. Our approach focuses on early diagnosis with a multidisciplinary team and management with bronchoscopy, bronchial blockers and use of extracorporeal membrane oxygenation. The choice of treatment depends on the site and origin of the hemorrhage, the availability of equipment and expertise, and the potential short- and long-term advantages and disadvantages.

Amaç: Bu çalışmada pulmoner endarterektomi sonrası hemoptizi gelişen hastalarımıza yaklaşım ve sonuçlarımız değerlendirildi. Çalışma planı: Mart 2011 ve Eylül 2017 tarihleri arasında 460 hastaya Kartal Koşuyolu Eğitim ve Araştırma Hastanesi’nde pulmoner endarterektomi uygulandı. Pulmoner endarterektomi sonrası masif akciğer kanamalı 10 hastanın (%2.1) (4 erkek, 6 kadın; ort. yaş 48.3±16.5 yıl; dağılım 21-76 yıl) klinik özellikleri, perioperatif tedavi ve ameliyat sonrası sonuçları değerlendirildi. Bulgular: Kronik tromboembolik pulmoner hipertansiyona ortalama tanı konulma süresi 17±13.6 ay idi. Tüm hastalar New York Kalp Cemiyeti fonksiyonel sınıf II (n=2), III (n=5) ya da IV (n=3) idi. Masif akciğer kanaması tedavisinde altı hastada (%60) ameliyat sırası ekstrakorporeal membran oksijenasyonu, dört hastada (%40) ise konservatif tedaviler kullanıldı. Hastane mortalitesi oranı %50 (n=5) idi; mortalite nedeni iki hastada septik şok, iki hastada çoklu organ yetmezliği ve bir hastada intrakranial kanama idi. Ekstrakorporeal membran oksijenasyonundaki iki hasta ve konservatif tedavi gören üç hastada sağkalım sağlandı. Sağ kalan tüm hastalarda fonksiyonel ve hemodinamik iyileşme gözlendi. Sonuç: Pulmoner endarterektomi sonrası masif akciğer kanaması insidansı göreceli düşük olmakla beraber, bu potansiyel olarak ölümcül bir komplikasyondur. Yaklaşımımız multidisipliner bir ekip ile erken tanı ve bronkoskopi, bronşiyal blokerler ve ekstrakorporeal membran oksijenasyonu kullanımı ile tedaviye odaklanmaktadır. Tedavi tercihi kanamanın yer ve kaynağına, eldeki araç ve deneyime ve olası kısa ve uzun dönem avantaj ve dezavantajlara bağlıdır.
Pulmoner endarterektomi sonrası masif akciğer kanamasının perioperatif tedavisi
Keywords: Kalp ve Kalp Damar Sistemi